Impact of COVID-19 on mental health of the elderly - Philip, Joel; Cherian, Vinu (International Journal Of Community Medicine And Public Health, 2020)
The COVID-19 pandemic has had an unprecedented effect on the lives of people, irrespective of social demographics. The elderly, however, face special challenges, and it is imperative that healthcare professionals identify and highlight their special needs so that they can be adequately protected and supported through these trying times. Unless care is taken, the elderly as a group may face significant fallout with regard to their mental and psychological wellbeing.